Synaptic and Extrasynaptic Glutamate Signaling in Ischemic Stroke - Chao, Naijian; Li, Sheng-Tian (Current Medicinal Chemistry, 2014)
Stroke is a leading cause of human mortality and disability where most cases of stroke are ischemic. The central nervous system (CNS) is extremely vulnerable to ischemic stroke particularly due to its unique ability: synaptic transmission. Not only does elaborate synaptic transmission consume extravagant energy that constrains neuronal viability under ischemic conditions, but glutamate, the most predominant neurotransmitter in the CNS, also triggers several catastrophic signaling cascades at both synaptic and extrasynaptic sites when excessively released. These signaling cascades accelerate neuronal death and exacerbate cerebral injuries during ischemic stroke. In this review, we discuss the complete picture of synaptic and extrasynaptic glutamate signaling in ischemic stroke. We hope to provide substantial insights into potential therapies by reviewing recent discoveries that have advanced our understanding of the complex glutamate signaling mechanisms in ischemic stroke.
Keywords: N-methyl-D-aspartate (NMDA) receptor